2007
DOI: 10.1200/jco.2007.25.18_suppl.10552
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer survival in carriers of BRCA1 and BRCA2 mutations

Abstract: 10552 Background: The characteristic pathologic features of breast cancers in women with a BRCA1 mutation suggest that women with hereditary breast cancer might have a worse than expected prognosis, but the results of clinical studies have been inconsistent. The current study is a national population-based study of Israeli women aimed at evaluating the impact of the inheritance of a BRCA1 or a BRCA2 mutation on breast cancer prognosis. Methods: All incident cases of invasive breast cancer diagnosed in Israel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Our results were in broad agreement with more recent studies, although others had reported conflicting results. [27][28][29][30][31][32] The percentage of BRCA-associated patients in our study (12.6%) was similar to a prior prospective cohort study, 33 The bold values derived from univariated analysis indicate that BRCA-mutation status and menopausal status might attribute to risk of contralateral breast cancer (CBC), however, only BRCA-mutation status confer to the independent risk factor of CBC.…”
Section: Discussionsupporting
confidence: 85%
“…Our results were in broad agreement with more recent studies, although others had reported conflicting results. [27][28][29][30][31][32] The percentage of BRCA-associated patients in our study (12.6%) was similar to a prior prospective cohort study, 33 The bold values derived from univariated analysis indicate that BRCA-mutation status and menopausal status might attribute to risk of contralateral breast cancer (CBC), however, only BRCA-mutation status confer to the independent risk factor of CBC.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies show better response to chemotherapy in BRCA1 carriers, the majority of whom had triple negative tumors and high grade disease; contradictory results were observed in BRCA2 carriers. 2,4,12,13 Whether hormone positive tumors in BRCA carriers respond better to chemotherapy remains to be determined.…”
Section: What's New?mentioning
confidence: 99%
“…Up to 10% of breast cancers (BC) are attributed to pathogenic mutations in the BRCA1 and BRCA2 genes. 1,2 While the majority of BC in BRCA1 carriers is triple negative, the rate of estrogen receptor (ER) positive BC in these patients is not negligible. Analysis of over 6000 BCs from BRCA carriers reported ER positive rates of 22% and 77%, among BRCA1 and BRCA2 mutation carriers, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations